DEMONSTRASI PEMERIKSAAN SADARI PADA WARGA BINAAN WANITA DI LEMBAGA PEMASYARAKATAN KELAS II B PADANGSIDIMPUAN - Nasution, Eva Yusnita; Tanjung, Wiwi Wardani (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Breast self-examination really needs to be known by a woman. The goal of breast self-examination is to detect early individual breast cancer symptoms. There are still many women who do not realize the importance of them having an early examination of their breasts. This community service activity is carried out to increase the knowledge of female assisted residents about breast self-examination. The problem that was found was that the demonstration of breast self-examination had never been carried out on female assisted residents in the Padangsidimpuan Class II B Penitentiary. Based on the results of interviews conducted with female assisted residents, they said that they had never heard of the term breast self-examination and also did not know the benefits of this action. Therefore, it is necessary to increase the knowledge of female assisted citizens in an effort to detect early breast cancer symptoms. The activity carried out in this PKM is a demonstration of breast self-examination. This activity aims to increase the knowledge of the assisted residents about breast self-examination and to detect early individual breast cancer symptoms. The result of this activity is that there is a change in the knowledge of female assisted residents about breast self-examination.